2006
DOI: 10.1097/01.aog.0000218096.54169.34
|View full text |Cite
|
Sign up to set email alerts
|

Parity, Mode of Delivery, and Pelvic Floor Disorders

Abstract: II-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
222
3
16

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 336 publications
(252 citation statements)
references
References 30 publications
11
222
3
16
Order By: Relevance
“…This ranks the severity of symptoms in four categories:. Mild (1-5 points), moderate (6)(7)(8)(9)(10)(11)(12), severe (13)(14)(15)(16)(17)(18), and severe (19)(20)(21). (11) In this study the overall average ICIQ-SF score was 9.9 points.…”
Section: Evaluation Of the Knowledge Of The Perineal Regionmentioning
confidence: 45%
See 1 more Smart Citation
“…This ranks the severity of symptoms in four categories:. Mild (1-5 points), moderate (6)(7)(8)(9)(10)(11)(12), severe (13)(14)(15)(16)(17)(18), and severe (19)(20)(21). (11) In this study the overall average ICIQ-SF score was 9.9 points.…”
Section: Evaluation Of the Knowledge Of The Perineal Regionmentioning
confidence: 45%
“…(13,14) However, it is stated that the greatest impact would be of gestation and type of delivery, which would jeopardize the PF by different mechanisms. (15,16) Some studies show that the UI is common during pregnancy. Sharma et al (17) evaluated 240 primiparae through the same questionnaire used in this study found the presence of urinary symptoms in about 48% of the women studied in the third quarter.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, CD is associated with longer hospital stays for both mother and baby [18,19], increased frequency of serious complications during future pregnancies [18], and higher costs [20]. Despite suggestions that elective CD might improve maternal perineal health [21,22], its long-term benefits are unproven [16,23], and its long-term risks have probably been minimized [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Urinary incontinence is the most prevalent pelvic floor dysfunction linked to birth (1) and is responsible for 16 billion dollars annual expense. (2) Stress urinary incontinence (SUI) affects 86% of incontinent women either alone (50%) or in conjunction with urge incontinence (36%).…”
Section: Introductionmentioning
confidence: 99%